Assessment of total cholesterol and uric acid level among postmenopausal women attending Chitwan Medical College Teaching Hospital - Ranabhat, Pashupati; Rimal, Brihaspati; Mandal, Fuleshor; koirala, Subash (Journal of Chitwan Medical College, 2025)
Introduction: This study aims to evaluate serum uric acid and total cholesterol concentrations among postmenopausal women. Method: A cross-sectional study was conducted over a five-month period, from Aug to Dec 2023, at Chitwan Medical College and Teaching Hospital (CMCTH), Bharatpur, Nepal. Ethical approval was obtained. A non-probability consecutive sampling technique was employed. Postmenopausal women were included, except those with known comorbidities (chronic kidney disease, cardiovascular disorders, or on medication for lipid-lowering or uric acid-altering therapy). Demographic and biochemical variables (age, serum total cholesterol, and serum uric acid levels) were gathered from lab records. Normality of continuous variables were checked. Descriptive and inferential statistics were applied, including Spearman's rank correlation and Pearson's chi-square test, with significance set at 5%. Result: Among the 165 postmenopausal women, the median age was 59 years, total cholesterol was 188 mg/dL, and uric acid was 5.20 mg/dL. Spearman correlation analysis revealed statistically significant positive correlations between age and uric acid (r=0.210, p=0.007) and between total cholesterol and uric acid (r=0.696, p<0.001). Conclusion: The study highlights elevated levels of uric acid and total cholesterol in postmenopausal women, with both markers showing positive associations with advancing age.